Associations of pathogenic variants in MLH1, MSH2, and MSH6 with risk of colorectal adenomas and tumors and with somatic mutations in patients with Lynch syndrome - Engel, Christoph; Ahadova, Aysel; Seppälä, Toni T.; Aretz, Stefan; Bigirwamungu-Bargeman, Marloes; Bläker, Hendrik; Bucksch, Karolin; Büttner, Reinhard; de Vos tot Nederveen Cappel, Wouter T.; Endris, Volker; Holinski-Feder, Elke; Holzapfel, Stefanie; et al. (Gastroenterology, 2020)
Lynch syndrome is caused by variants in DNA mismatch repair (MMR) genes and associated with an increased risk of colorectal cancer (CRC). In patients with Lynch syndrome, CRCs can develop via different pathways. We studied associations between Lynch syndrome-associated variants in MMR genes and risks of adenoma and CRC and somatic mutations in APC and CTNNB1 in tumors in an international cohort of patients.